Nutritional status and skeletal muscle status in patients with head and neck cancer: Impact on outcomes - Merran Findlay; Kathryn White; Chris Brown; Judith D. Bauer (Wiley, 2021)
Abstract Background Computed tomography (CT)‐defined skeletal muscle depletion and malnutrition are demonstrated as poor prognostic factors in patients with head and neck cancer (HNC), however to date, have only been explored in isolation. We aimed to describe body composition profile and examine the impact of nutritional status as well as independently and concurrently occurring body composition features on overall survival, treatment completion, unplanned admissions and length of stay (LOS) in patients undergoing radiotherapy (RT) or chemoradiotherapy (CRT) of curative intent for HNC. Methods This work is a retrospective, observational study of patients who had completed treatment of curative intent for HNC. Scored Patient‐Generated Subjective Global Assessment (PG‐SGA) was used to determine nutritional status. Tissue‐density data were derived at the third lumbar vertebra (L3) with sarcopenia and myosteatosis defined by published, sex‐specific threshold values stratified by body mass index for skeletal muscle index (cm2/m2) and skeletal muscle radiodensity (SMR, Hounsfield Unit). Results Pre‐treatment data (n = 277: 78% male, mean (SD) age 60 (13) years) revealed the prevalence of malnutrition (24.9%), sarcopenia (52.3%), myosteatosis (82.3%), and concurrently occurring sarcopenia and myosteatosis (39.7%). Malnutrition was independently associated with reduced OS for patients with moderate [hazard ratio (HR) 2.57; 95% confidence interval (CI) 1.45-4.55, P = 0.001] and severe (HR 3.19; 95% CI 1.44-7.07, P = 0.004) malnutrition on multivariable analysis but not sarcopenia (HR 1.09; 95% CI 0.70-1.71), P = 0.700 or myosteatosis (HR 1.28; 95% CI 0.57-2.84), P = 0.500). Malnutrition was associated with treatment discontinuation (P < 0.001), not completing RT as planned (P < 0.001), unplanned hospital admission (P = 0.021), and greater LOS (P < 0.001). Skeletal muscle status features were associated with unplanned hospital admissions for those with no features (32%), with sarcopenia only (50%), myosteatosis only (25%), and concurrent sarcopenia and myosteatosis (50%), P < 0.001. Similarly, a clinically relevant greater median (Q1, Q3) LOS was observed for those with sarcopenia only [5 (3, 32)], myosteatosis only [10 (5, 30)], concurrent sarcopenia, and myosteatosis [14 (4, 33)] days vs. those with no features [3 (2, 11)] days, P = 0.2. Conclusions Malnutrition was a more powerful prognostic indicator than CT‐defined skeletal muscle depletion and was independently associated with reduced OS in patients undergoing RT or CRT of curative intent for HNC. CT‐defined skeletal muscle depletion studies should recognize the multifaceted nature of human body composition and also measure nutritional status using validated methods in order to move towards developing a typology of high risk criteria for this complex patient group.